TYK2 Kinase Activity Is Required for Functional Type I Interferon Responses In Vivo - Prchal-Murphy, Michaela; Semper, Christian; Lassnig, Caroline; Wallner, Barbara; Gausterer, Christian; Teppner-Klymiuk, Ingeborg; Kobolak, Julianna; Müller, Simone; Kolbe, Thomas; Karaghiosoff, Marina; Dinnyés, Andras; Rülicke, Thomas; et al. (PLOS ONE, 2012)
Tyrosine kinase 2 (TYK2) is a member of the Janus kinase (JAK) family and is involved in cytokine signalling. In vitro analyses suggest that TYK2 also has kinase-independent, i.e., non-canonical, functions. We have generated gene-targeted mice harbouring a mutation in the ATP-binding pocket of the kinase domain. The Tyk2 kinase-inactive (Tyk2K923E) mice are viable and show no gross abnormalities. We show that kinase-active TYK2 is required for full-fledged type I interferon- (IFN) induced activation of the transcription factors STAT1-4 and for the in vivo antiviral defence against viruses primarily controlled through type I IFN actions. In addition, TYK2 kinase activity was found to be required for the protein’s stability. An inhibitory function was only observed upon over-expression of TYK2K923E in vitro. Tyk2K923E mice represent the first model for studying the kinase-independent function of a JAK in vivo and for assessing the consequences of side effects of JAK inhibitors.